Fluorescence Detection of Etoposide-loaded Nanoparticles by HPLC and Pharmacokinetics Study - Yang, H.-Z.; Liu, L.; Xu, X. (Arzneimittelforschung, 2012)
A simple HPLC with fluorescence detection method was developed for determination and pharmacokinetic study of Etoposide in dog plasma.Plasma sample pretreatment involved liquid-liquid extraction of 500 µL plasma. The chromatographic separation was carried out on a Gemini C18 column with a mixture of methanol (A) and water (B) (0~5 min, volume of A was 45–50%, 5~10 min, volume of A was 50–90%) used as mobile phase at a flow rate of 0.4 ml/min.These results indicated that the accuracy and precision of the current assay were within the recommendations for assay validation as stipulated in “Guidance for Industry: Bioanalytical Method Validation”. Etoposide nanoparticles and injection pharmacokinetic parameters were as follows: T1/2, 2.26 (0.71) and 1.74 (0.43) h;Cmax, 13.24 (5.32) and 8.12 (3.61) µg/ml; AUC0-t, 41.32 (7.33) and 16.53 (4.12) µg · ml − 1 · h; AUC0–∞, 49.54 (9.62) and 19.64 (8.22) µg · ml − 1 · h; MRT, 3.13 (0.54) and 2.06 (0.33) h and CL 7.35 (1.53) and 12.61 (2.22), respectively.This method was fully validated and successfully applied to a preclinical pharmacokinetic study of Etoposide in dogs after i. v. drip administration.
Keywords: etoposide; nanoparticles; HPLC; pharmacokinetic